Natural law and human rights: toward a recovery of practical reason - Manent, Pierre (Catholic ideas for a secular world, 2020)
Foreword : Natural Law and the Restoration of Practical Reason / Daniel J. Mahoney -- Translator's Introduction / Ralph C. Hancock -- Why Natural Law Matters -- Counsels of Fear -- The Order of the State without Right or Law -- The Law, Slave to Rights -- The Individual and the Agent -- Natural Law and Human Motives -- Appendix : Recovering Law's Intelligence.